Analisis Beban Kerja Pada Instalasi Gizi Dengan Metode WISN di Rumah Sakit X - Sheva Arlinda; Wiwik Kusumawati; Yeni Prawiningdyah (Jurnal Admmirasi, 2019)
This study analyzes the workload to understand the optimal number of needs in the installation of nutrition to support hospital operations according to needs, both in terms of type and development. Excess of labor will spend more unproductive work time, as opposed to labor will spend excessive workload. Method: This study used a mixed method, Quantitative research by observation with WISN and proceed with qualitative research using indepth interviews The results showed that the workload on expert services was 53.7%, on the processing or cooker services was 50.4% and the presenter was 44%. Obtained the amount of available work time of 115,920 minutes for one year in the nutrition installation of PKU Muhammadiyah Hospital Bantul. There are 4 categories of activities or activities in the nutrition installation, namely direct activities, indirect activities, personal activities and non-productive activities in the nutrition installation of PKU Muhammadiyah Hospital Bantul. Conclusion: The optimal number of employees in nutritional department PKU Muhammadiyah Hospital Bantul is 24 people of employees. This means that there are an insufficiency number of nutritionist are 2 people and 1 person excess food services.